2016
DOI: 10.1007/s00446-016-0277-8
|View full text |Cite
|
Sign up to set email alerts
|

Determining majority in networks with local interactions and very small local memory

Abstract: Abstract. We study here the problem of determining the majority type in an arbitrary connected network, each vertex of which has initially two possible types (states). The vertices may have a few additional possible states and can interact in pairs only if they share an edge. Any (population) protocol is required to stabilize in the initial majority, i.e. its output function must interpret the local state of each vertex so that each vertex outputs the initial majority type. We first provide a protocol with 4 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 26 publications
0
45
0
Order By: Relevance
“…Then in [5] the authors have completely characterized the computational power of the model by establishing the equivalence between predicates computable in the population model and those that can be defined in the Presburger arithmetic. Since then, there has been a lot of work on population protocols including the majority problem [2,6,12,14,17], the leader election problem [9,15], in presence of faults [11], and on variants of the model [10,13].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Then in [5] the authors have completely characterized the computational power of the model by establishing the equivalence between predicates computable in the population model and those that can be defined in the Presburger arithmetic. Since then, there has been a lot of work on population protocols including the majority problem [2,6,12,14,17], the leader election problem [9,15], in presence of faults [11], and on variants of the model [10,13].…”
Section: Related Workmentioning
confidence: 99%
“…n A < n B ). In [12,14] the authors propose a four-state protocol that solves the majority problem with a convergence parallel time logarithmic in n but only in expectation. Moreover, the expected convergence time is infinite when n A and n B are close to each other (that is γ approaches 0).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…We next considered CRNs with four species, to explore how many reactions are required to stably compute the majority specification. There is a known CRN (or population protocol) with four species that stably computes the majority problem with three reactions and four species [ 44 46 ]. Indeed, it has been shown that four species are necessary [ 35 , 46 ] to stably compute majority.…”
Section: Resultsmentioning
confidence: 99%
“…There is a known CRN (or population protocol) with four species that stably computes the majority problem with three reactions and four species [ 44 46 ]. Indeed, it has been shown that four species are necessary [ 35 , 46 ] to stably compute majority. However, this known CRN does not satisfy Ψ Maj .…”
Section: Resultsmentioning
confidence: 99%